DEVELOPMENT OF ROBUST WATER FILTRATION SYSTEM - Amir Azman, Muhamad Haziq Zikri (IRC, 2019)
This continuance of using natural and clean water is no longer tolerable as a step towards a sustainable future. This study emphasizes the importance of water treatment developing a robust water filtration system through selecting the most suitable adsorbents to be used as the filter media by using 4 different adsorbents as well various different arrangements; coconut-based granular activated carbon, fine sand, oil palm empty fruit bunch and non-woven geotextile.